1998
DOI: 10.1001/jama.280.7.623
|View full text |Cite
|
Sign up to set email alerts
|

National Use and Effectiveness of β-Blockers for the Treatment of Elderly Patients After Acute Myocardial Infarction

Abstract: Context.-Despite the importance of ␤-blockers for secondary prevention after acute myocardial infarction (AMI), several studies have suggested that they are substantially underutilized, particularly in older patients.Objectives.-To describe the contemporary national pattern of ␤-blocker prescription at hospital discharge among patients aged 65 years or older with an AMI, to identify the most important predictors of the prescribed use of ␤-blockers at discharge, and to determine the independent association betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
255
5
7

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 459 publications
(283 citation statements)
references
References 19 publications
16
255
5
7
Order By: Relevance
“…29 There is some controversy regarding the use of intravenous (IV) β-blockers in acute STEMI in the elderly with some trials concluding that there is a significant reduction in mortality in the elderly subgroup compared to younger patients. 30 The COMMIT trial concluded that IV metoprolol did not result in a reduction in all-cause mortality or the composite end point of death, MI, or cardiac arrest in the elderly, and there was a trend towards increased rates of congestive heart failure (CHF) and cardiogenic shock.…”
Section: β β β-Blockersmentioning
confidence: 99%
See 1 more Smart Citation
“…29 There is some controversy regarding the use of intravenous (IV) β-blockers in acute STEMI in the elderly with some trials concluding that there is a significant reduction in mortality in the elderly subgroup compared to younger patients. 30 The COMMIT trial concluded that IV metoprolol did not result in a reduction in all-cause mortality or the composite end point of death, MI, or cardiac arrest in the elderly, and there was a trend towards increased rates of congestive heart failure (CHF) and cardiogenic shock.…”
Section: β β β-Blockersmentioning
confidence: 99%
“…Most of these trials have excluded patients greater than 75 years of age, but multiple observational studies provide strong evidence that long-term β-blockade after ACS improves outcomes in patients up to 90 years of age. 29 …”
Section: β β β-Blockersmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] Use of beta blockers is influenced by many factors, such as patient age, geographical location, visits to cardiologist or internist versus family or general practitioner, race, and health care system characteristics. [11][12][13][14][15][16][17][18][19][20] Temporal variability in the use of beta blockers has been documented. 11,17,19 Calcium-channel blockers and/or long-acting nitrates can be added to beta blockers or replace them if beta blockade is contraindicated or poorly tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…As outlined in these therapeutic guidelines, antiplatelet, antihypertensive, and lipid-lowering therapies are known to significantly reduce the risk of recurrence of macrovascular diseases, such as coronary and cerebrovascular diseases. Contrary to this, national and international studies have shown that these guidelines are not yet fully implemented in primary and secondary prevention with respect to platelet aggregation inhibitors, angiotensin-converting enzyme (ACE) inhibitors, betablockers, and statins (EUROASPIRE I and II Group 2001;Krumholz et al 1998;Welterman et al 1997) in the prevention of ACS. However, long-term secondary stroke prevention in Germany has revealed better findings, especially with regard to antithrombotic medications (Hamann et al 2003).…”
Section: Introductionmentioning
confidence: 99%